Analiza porównawcza wskaźników oceny sytuacji finansowej gmin. Koncepcja i zastosowanie = Comparative analysis of financial situation assessment indicators of municipalities. Concept and application - Hermaszewski, Jarosław (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The deteriorating financial situation of local government units forces the authorities to seek solutions to streamline decision processes. Taking the right decision about the direction of spending public funds should be preceded by an economic analysis providing guidance on how to increase the effectiveness of public management. In well-functioning business organizations the comparative analysis is one of the most important economic analyses.
Keywords: gmina; finanse; analiza porównawcza; informacja publiczna